Double glassy states and large spontaneous and conventional exchange bias in La1.5Ca0.5CoFeO6 ferrimagnetic double perovskite. (14th September 2022) - Singh, Prajyoti; Singh, Rahul K; Dixit, Srishti; Patel, Neha; Alam, Mohd; Dan, Sambhab; Jain, A; Anand, K; Gangwar, Vinod K; Singh, Rahul; Joshi, Amish G; Yusuf, S M; et al.
Abstract: The structural and magnetic properties of hole doped double perovskite La1.5 Ca0.5 CoFeO6 have been investigated by measuring x-ray photoemission spectroscopy, neutron powder diffraction and magnetization. A ferrimagnetic transition is observed at T C ∼ 167 K. The presence of anti-site disorder (ASD) in La1.5 Ca0.5 CoFeO6 has also been demonstrated. Double re-entrant cluster glass transitions ( T 1 ∼ 11 K and TS ∼ 35 K) were observed which has been attributed to the ASD effect. The presence of both large spontaneous exchange bias H SEB ∼ 2.106 kOe and giant conventional exchange bias H CEB ∼ 1.56 T at 5 K has also been observed which can be attributed to the coexistence of long range magnetic ordering and glassy state. The experimental observations were explained with the results obtained by the density functional theory calculation. The presence of double glassy states, large exchange-bias effect and different magnetic phases make this system a potential candidate for spintronic applications.